Individual dietary diversity score dan kejadian stunted pada anak prasekolah di Kota Padang - Idral Purnakarya; Sri Ramayanti; Desy Purnama Sari (Jurnal Gizi Klinik Indonesia)
Individual dietary diversity score and stunted in preschool children in Padang